2020
DOI: 10.12890/2020_001356
|View full text |Cite
|
Sign up to set email alerts
|

A First Sign Not to be Missed: Cutaneous Metastasis from Breast Cancer

Abstract: Cutaneous metastasis has a frequency of 1 to 10% among all metastatic cancer forms and breast cancer accounts for 30% of all cases. We report the case of a 73-year-old woman who presented with 4 skin lesions distributed across the upper trunk and abdomen; these had developed over a period of 12 months. Over the previous 6 months she had also developed anorexia, asthenia and weight loss. Upon investigation, a nodular mass was found in the left breast. Skin and breast mass biopsy were performed. Histology confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 4 publications
0
10
0
5
Order By: Relevance
“…A limitation of this study was that sampling for histopathological examination was performed only on skin lesions. For the definite diagnosis, metastasis should show histopathological similarities to the primary tumor to determine whether the primary tumor is of origin [14]. However, in this study, the definitive diagnosis of lesions originating from the mammary gland was confirmed by the correlation between histopathological findings with evidence of lymphatic invasion and history of MGT.…”
Section: A B Cmentioning
confidence: 75%
“…A limitation of this study was that sampling for histopathological examination was performed only on skin lesions. For the definite diagnosis, metastasis should show histopathological similarities to the primary tumor to determine whether the primary tumor is of origin [14]. However, in this study, the definitive diagnosis of lesions originating from the mammary gland was confirmed by the correlation between histopathological findings with evidence of lymphatic invasion and history of MGT.…”
Section: A B Cmentioning
confidence: 75%
“…Cutaneous metastasis has a frequency of up to 10% among all metastatic cancer forms, with breast cancer being the most common, accounting for 30% of all cases. 1 Thus, when a patient with a history of estrogen receptor-positive (ER+) breast cancer presents with an ER + cutaneous metastases, it is common to assume breast cancer recurrence. However, some lung adenocarcinomas can be ER +.…”
Section: Introductionmentioning
confidence: 99%
“…Cutaneous metastases are rare, reportedly occurring in 0.7 to 10% of malignancies, and most commonly occur due to breast carcinoma in women. 1 Herein, we describe a case of cutaneous metastases as the initial presentation of a recurrent breast adenocarcinoma.…”
mentioning
confidence: 99%
“…CMBC accounts for approximately 33% of cutaneous metastases, occurring at a reported rate of 2.5% per primary breast malignancy. 1 Cutaneous metastases spread contiguously or by distant metastasis via lymphatic or hematogenous routes. 2 CMBC typically presents as 1-3 cm painful, pruritic, or asymptomatic firm, pink to reddish-brown, erythematous nodule or plaque on the chest, abdomen, or scalp, as in our patient.…”
mentioning
confidence: 99%